Serum Bilirubin Level and Associated Factors in Patients of Self Reporting Jaundice without Evidence of Clinical Jaundice (Medicine Today, 2022)
Introduction with objective: This study was done to see the serum bilirubin level of patients with self reporting jaundice without clinical jaundice.Materials and Methods: This study was done from January 2019 to January 2020 at Popular Medical Centre, Sylhet. Consecutive patients claiming to have jaundice without clinical icterus were included. Demographical information and presenting symptoms were noted. Serum bilirubin and relevant laboratory investigations were done and results were noted. Statistical analysis was done using SPSS 20.Results: Total 177 patients, age varying from six years to 80 years (mean 28.54) were included. Of them 134 (75.7%) were male. Common symptoms for were anorexia (90; 50.8%), pain abdomen (76; 42.9%), weakness (49; 27.7%), nausea (45; 25.4%), fullness of abdomen (35; 19.8%), gas (34; 19.2%) and vomiting (16; 9%). Of them 164 (92.7%) initially visited kabiraj. Serum bilirubin level of them varied from 0.04 mg/ dl to 2.67 mg / dl (mean 0.814±0.577) and ALT level varied from 10 iu/ dl to 2944 iu/ dl (mean 71.55±270.09). In this series 143 (80.0%) patients had no jaundice biochemically. Among others, 08 (4.52%) were case of acute hepatitis and 13 (7.34%) were possible cases of Gilbert’s syndrome. Patients’ attitude regarding informal caregivers significantly differed with education level.Conclusion: Most of patients claiming to have jaundice without icterus had no evidence of liver disease. Consulting kabiraj they are wasting money and sometimes inviting health related disasters. So mass education and motivation may increase awareness of people regarding liver disease and prevent health hazards.Medicine Today 2022 Vol.34(1): 01-05